Potential of Cocoa Flavanols in Improving Cardiovascular Adaptation and Exercise: A Scoping Review - Arya Dwi Handana; Yulia Lanti Retno Dewi; Sinu Andhi Jusup (GLOBAL HEALTH SCIENCE GROUP, 2025)
Cardiovascular fitness, quantified as maximal oxygen consumption (VO₂Max), is a significant indicator of exercise tolerance and cardiovascular health. Sedentary behavior and aging are determinants that contribute to endothelial dysfunction, arterial stiffness, and reduced cardiac output, leading to a decline in VO₂Max. Cocoa Flavanols (CFs), rich in (−)-epicatechin, have been found to enhance endothelial function, nitric oxide bioavailability, and reduce blood pressure and hence might be beneficial for cardiovascular adaptation and VO₂Max improvement. This scoping review explores the potential of CFs to enhance cardiovascular function and exercise tolerance. Method: Two randomized controlled trials were employed in this scoping review. The first trial examined the effect of 30-day CF supplementation (1000 mg/day) on cardiorespiratory fitness in healthy elderly adults. The second trial examined the effect of 7-day CF supplementation (400 mg/day) on pulmonary oxygen uptake kinetics and exercise tolerance in middle-age sedentary adults. Results: In older adults, CF supplementation improved VO₂peak, oxygen pulse, exercise capacity, and endothelial function and lowered blood pressure in middle-aged sedentary adults, CFs improved VO₂ kinetics during moderate-intensity exercise, indicating enhanced oxygen delivery, but not exercise tolerance during severe-intensity exercise. Such results highlight CFs' positive effects on vascular health and efficiency of moderate-intensity exercise. Conclusion: Cocoa flavanols may enhance cardiovascular adaptation and exercise performance by improving endothelial function, reducing arterial stiffness, and optimizing oxygen uptake during exercise. Further studies are required to evaluate their effect on maximal exercise performance and long-term cardiovascular outcomes.